2012
DOI: 10.1155/2012/978019
|View full text |Cite
|
Sign up to set email alerts
|

Pollination Requirements and the Foraging Behavior of Potential Pollinators of Cultivated Brazil Nut (Bertholletia excelsaBonpl.) Trees in Central Amazon Rainforest

Abstract: This study was carried out with cultivated Brazil nut trees (Bertholletia excelsaBonpl., Lecythidaceae) in the Central Amazon rainforest, Brazil, aiming to learn about its pollination requirements, to know the floral visitors of Brazil nut flowers, to investigate their foraging behavior and to determine the main floral visitors of this plant species in commercial plantations. Results showed thatB. excelsais predominantly allogamous, but capable of setting fruits by geitonogamy. Nineteen bee species, belonging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 12 publications
(16 reference statements)
1
36
0
3
Order By: Relevance
“…The predominance of outcrossing in B. excelsa was previously reported in a study on the mating system using genetic markers (O'Malley et al, 1988;Wadt et al, 2015). In contrast, a study of the species based on hand pollination showed that self-fertilization did not result in fruit production, suggesting that the species is self-incompatible or presents inbreeding depression (Cavalcante et al, 2012). However, self-incompatibility may be latent or vary by an individual due to genetic mechanisms, meaning that at some stages of tree fertility self-fertilization may occur or some trees may be selfcompatible allowing self-fertilization to occur.…”
Section: Mating Systemmentioning
confidence: 66%
See 3 more Smart Citations
“…The predominance of outcrossing in B. excelsa was previously reported in a study on the mating system using genetic markers (O'Malley et al, 1988;Wadt et al, 2015). In contrast, a study of the species based on hand pollination showed that self-fertilization did not result in fruit production, suggesting that the species is self-incompatible or presents inbreeding depression (Cavalcante et al, 2012). However, self-incompatibility may be latent or vary by an individual due to genetic mechanisms, meaning that at some stages of tree fertility self-fertilization may occur or some trees may be selfcompatible allowing self-fertilization to occur.…”
Section: Mating Systemmentioning
confidence: 66%
“…The IBD pollen dispersal pattern can be explained by the behavior of pollinating bees. B. excelsa is pollinated by medium and large bees of the Bombus, Centris, Xylocopa, and Epicharis genera, as well as some species of Euglossinae (Maués, 2002;Cavalcante et al, 2012). While these species can fly over long distances, they forage within restricted areas when there are many trees flowering, thus resulting in short distance pollen dispersal (Janzen, 1971).…”
Section: Pollen Dispersalmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the fungus thrives when nuts remain on the forest floor for extended periods of time (Hudler 1998), Brazil nut producers are encouraged to dry nuts post-harvest to avoid contamination. The construction of drying structures became part of a series of 'best management practices' outlined in the extension literature (Cardó 2000;Wadt et al 2005;APIZ 2008). While FSC standards for Brazil nuts have been developed in Brazil, Peru and Bolivia, there are few experiences of FSC certification on the ground, since it is perceived as costly as it attempts to cover too many forest management dimensions for what is considered a non-destructive harvesting activity (Duchelle et al 2014b).…”
mentioning
confidence: 99%